Acciones independientes de enfermería en el postoperatorio mediato de pacientes con endocarditis infecciosa - Ramos León, Yusnei; Caro Domínguez, Georgina; Morales Ramón, Ana M. (CorSalud, 2018)
Acciones independientes de enfermería en el postoperatorio mediato de pacientes con endocarditis infecciosa